How much is that doggie in the window? - Trapani, Iza.; Merrill, Bob. (Watertown, MA : Charlesbridge, 2004)
An illustrated adaptation of the classic children's song in which a young boy, unable to save for the puppy he wants because he keeps helping other people, gets a very special reward.
Book Links (A.L.A.)
School Library Journal
3.5
K-3.
K-3
Keywords: Children's songs -- Texts; Dogs -- Songs and music -- Texts; Money -- Songs and music -- Texts; Dogs -- Songs and music; Money -- Songs and music; Songs; Dogs -- Songs; Money -- Songs; Songs